Pengaruh Kompetensi, Kecerdasan Emosional dan Integritas Terhadap Kinerja Perangkat Desa - Inka Nuromavita; Muhammad Syaqiq (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this research is to analyze competence, emotional intelligence and integrity on the performance of village officials in Subah sub-district. This sampling method used a saturated sampling technique and the number of samples in this study was 80 respondents who came from the villages of Teggulang Harjo, Keborangan, Menjangan and Karang Tengah. The data used was primary data. Data was obtained directly from village officials through questionnaires. Primary data is processed and then analyzed using SPSS. The collected data was then analyzed using multiple linear regression. The results of this research show that Competence has a positive and significant effect on performance, Emotional Intelligence has a positive and significant effect on performance, Integrity has a positive and significant effect on performance.